2022
DOI: 10.1038/s41467-022-31760-z
|View full text |Cite
|
Sign up to set email alerts
|

Desymmetrization of N-Cbz glutarimides through N-heterocyclic carbene organocatalysis

Abstract: Over the past decade, the catalysis of N-heterocyclic carbenes has achieved significant advances. In this area, aldehydes, enals, and esters, are commonly employed as starting materials through various catalytic activation modes. However, NHC-activated strategy of amide and its derivatives remains elusive. Described herein is the realization of asymmetric desymmetrization of N-Cbz glutarimides with alcohols through an imide C-N bond cleavage under NHC organocatalysis. A structurally diverse set of enantioenric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…of the base led to a dramatic loss of the yield (entries 9 and 10). Screening of solvents found no better solvent than THF (entries [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of the base led to a dramatic loss of the yield (entries 9 and 10). Screening of solvents found no better solvent than THF (entries [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…10 Recently an example of N -Cbz glutarimide desymmetrization via the ring-opening attack of imides by NHC was reported by the Fu group. 11 Esters can be attacked by NHC to realize transesterification 12 or amidation 13 reactions. The Chi group demonstrated an array of enantioselective α-, β-, and γ-functionalization reactions of para -nitro phenyl esters.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, all computations were carried out using the Gaussian 16 program. 35 Due to the reliability of density functional theory in the mechanistic studies of organocatalytic reactions, [36][37][38][39][40][41][42][43] enzyme catalyzed reactions 44 and transition metal-catalyzed reactions, [45][46][47][48][49][50]…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, all computations were carried out using the Gaussian 16 program. 35 Due to the reliability of density functional theory in the mechanistic studies of organocatalytic reactions, 36–43 enzyme catalyzed reactions 44 and transition metal-catalyzed reactions, 45–50 we have performed DFT calculations at the M06-2X (ref. 51 and 52)/6-311++G(d,p)/IEF-PCM HFB (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the mechanisms and selectivities of these transformations have been extensively explored by us and others. 8 Recently, Chi and co-workers made significant contributions to the field of NHC organocatalysis, particularly in the area of activating saturated carbonyl compounds. 9 Their work has helped to expand the scope of NHC-catalyzed reactions and led to the development of new and more efficient catalytic systems, whereas recent studies have shown that NHC-bounded intermediates do not always work as nucleophiles in reactions with saturated carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%